Verkörperungen des Sozialen: Neophänomenologische Grundlagen und soziologische Analysen - Gugutzer, Robert (transcript, 2014)
Social reality is not only, as the sociological mainstream suggests, the result of rationally and norm-oriented acting individuals. Rather, it is just as much the product of the interaction of embodied subjects. Body is a fundamental condition for the constitution and construction, representation and reproduction of sociality. On the basis of New Phenomenology, Robert Gugutzer develops cornerstones of a neo-phenomenological sociology and presents »embodiment« as a basic sociological concept. Using six case studies on sport, dance, film, religion, education and identity as examples, the untapped cognitive potential of a body-based sociology is illustrated.